The Effect of Borax Addition as Buffering Agent on Storage Stability of Melamine-Formaldehyde Resin in the Production of High-Pressure Laminates - Muslem, Abdul Halim; Rahmi, Rahmi; Fujiani, Midia (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2023)
High-pressure laminates (HPL) is one of the applications of thermosetting resins for wood-based materials as protective and decorative panels covering building furniture. Melamine-formaldehyde (MF) resin is one of the resins that play a role in the production of high-pressure laminates. This resin has low storage stability due to cross-linking between free melamine methylols accompanied by a decrease in pH during the storage process. This study aims to improve the storage stability of melamine-formaldehyde resin by adding borax as a buffering agent. Synthesis of MF resin was conducted by polymerization and condensation steps followed by the addition of borax at concentrations of 0, 0.5, 1, 1.5, and 2% when the endpoint was reached. The characterization of the resin includes the analysis of the physical and chemical parameters of the resin and the analysis of the functional groups of the resin by FT-IR. Storage stability study of MF resin was carried out by daily visual observation and determination of daily changes in pH and viscosity. MF resin was further used in the production of high-pressure laminates. High-pressure laminates characterization includes quality analysis based on SNIISO4586-7:2017 and analysis gloss level. In this study, 1.5% MF borax resin had the highest storage stability, namely 11 days. HPL quality analysis complies with SNIISO4586-7:2017 standards. High-pressure laminates of 1.5% borax MF resin has the highest gloss level, which is 115.